(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The problem of teaching speech etiquette and culture of speech in a foreign language is one of the most interesting, but not fully studied. The article makes a clear and detailed analysis of the process of forming correct and cultured speech in a foreign language. Attention is drawn to the question of factors that directly affect the formation of a person’ speech culture. The practical value of the work consists in the opportunity to apply the results of the conducted research in the further professional activities of graduate students of language faculties in their communication with foreign partners, tourists and in international cooperation. The expansion of scientific relations, visits of specialists abroad in order to study the experience of foreign colleagues to participate in international scientific symposiums and conferences also increases the demand for proficiency not only in a foreign language itself, but also in cultural communication.